Valerius Flaccus, Argonautica, Book VI : a commentary - Wijsman, H. J. W. (Mnemosyne, Supplements, 2000)
In spite of an increased interest over the last ten years in the 1st century AD Roman poet Valerius Flaccus, involving the production of several commentaries, part of his work Argonautica was still lacking a modern commentary. This book gives a full philological and literary commentary of the turbulent book VI of the Argonautica . The Silver Latin author's peculiar phraseology and choice of words is highlighted. Where possible the poem is interpreted in the context of the other Silver Latin epic poets.